Heterogenous Mental Health Impacts of a Forced Relocation: The Red Zone in Christchurch after Its 2011 Earthquake - Thoa Hoang; Van Thinh Le; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2024)
People are sometimes forced to move, and it has often been hypothesised that such relocation involves significant psychological costs. The challenge in identifying the mental health consequences of moving is that most moves are (partly) voluntary. We use a natural experiment, the mandated relocation of some households after an exogenous shock, to identify the causal impact of moving on people's mental health. The event we focus on is the 2011 Christchurch (New Zealand) earthquake, and the consequent decision of the central government to relocate about 8000 households from some of the affected area. We use a comprehensive administrative dataset that includes health records with information on hospital attendance, specialist services, and prescribed medications for (almost) every resident in the city. We find a statistically significant increase in the likelihood and frequency of receiving treatment for moderate mental health problems among individuals compelled to relocate, when compared to other residents of the earthquake-affected city who were allowed to remain in situ. This increase persisted to December 2013 for everyone but remained significant for the elderly across the whole examined period to the end of 2018. We found no such increase for more severe mental health incidents that required more acute interventions.
Keywords: I10; Q54; 330; mental health; managed retreat; disaster risk; relocation; difference-in-difference